Almost Married - Bucak, Fatma; Fergnachino, Sergio (Turkey; Italy; Francesca Portalupi for Zenit Arti Audiovisive, 2010)
Fatma is a 25 years old Turkish woman. To live a free life from the traditional ties of her family and father she runs to Italy. Here she studies photography, taking on an exciting, new, independent life. And of course she fell in love with an Italian, Davide, with whom she lives happily. But what to tell her Turkish family?
Verzio Film Festival Submission
Keywords: Documentary films